2006
DOI: 10.1063/1.2354082
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure of C60 on Au(887)

Abstract: We present an analysis of the electronic structure of C60 adsorbed on a vicinal Au(111) surface at different fullerene coverages using photoemission, x-ray absorption, and scanning tunneling microscopy/spectroscopy (STS). STS provides a straightforward determination of the highest occupied molecular orbital (HOMO) and the lowest unoccupied molecular orbital (LUMO) levels with respect to the Fermi energy. At C60 coverages of 0.5 and 1 ML a 2.7 eV wide HOMO-LUMO gap is found. The near-edge x-ray absorption fine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
31
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 43 publications
8
31
0
Order By: Relevance
“…The spectra recorded from molecules with identical orientations did not depend on orientations of the nearest neighbour molecules. The assignment of the HOMO, LUMO, LUMO + 1, and LUMO + 2 to spectral signatures shown in figure 2(a) is based on published results [7,16]. The orbital energies of both C 60 types are summarized in table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The spectra recorded from molecules with identical orientations did not depend on orientations of the nearest neighbour molecules. The assignment of the HOMO, LUMO, LUMO + 1, and LUMO + 2 to spectral signatures shown in figure 2(a) is based on published results [7,16]. The orbital energies of both C 60 types are summarized in table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Dividing by the throughput can then cause new structure in the data to arise, often centered near 284 eV, as we suggest to be the case in Ref. 1. A second aspect of the presented 0.5 and 1 ML spectra is the falling intensity at high photon energies, which would typically stem from the same kind of faulty correction.…”
mentioning
confidence: 99%
“…Phys. 127, 067101 "2007… ‡" F. Schiller 2 and suggested that the throughput correction and the Fermi level placement are erroneous. Below, we rule out both scenarios.…”
mentioning
confidence: 99%
“…In the 0.5 ML C 60 near-edge x-ray absorption fine structure ͑NEXAFS͒ spectra the first peak is interpreted as the signature of the C 60 lowest unoccupied molecular orbital ͑LUMO͒. 2 Scanning tunneling spectroscopy reveals that the LUMO is placed roughly 1 eV above the Fermi level. Therefore, we conclude that the Fermi energy does not coincide with the carbon 1s binding energy as proposed by Schiessling and Brühwiler 1 X-ray absorption data in thin C 60 films are influenced by excitonic effects as previously reported by, e.g., Schwedhelm et al 4 This work is consistent with our conclusion that the Fermi level is located Ϸ0.8 eV below the LUMO peak for the C 60 monolayer.…”
mentioning
confidence: 99%